2002
DOI: 10.1161/01.hyp.0000041221.13644.b9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Inhibition Attenuates Lipopolysaccharide-Induced Cardiovascular Failure

Abstract: Abstract-The present study aimed to determine the relevance of cyclooxygenase-2 (COX-2)-derived prostanoids for the adverse effects of lipopolysaccharides (LPSs) on cardiovascular function. For this goal, male Sprague-Dawley rats received a single intravenous dose of LPS (10 mg/kg) and were treated with different cyclooxygenase inhibitors. Injection of LPS caused a marked decrease of systolic arterial pressure, from 128 to 79 mm Hg, and a concomitant increase of heart rate, from 380 to 530 minutes Ϫ1 . Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 61 publications
7
46
0
Order By: Relevance
“…Concomitantly, we detected an enhanced expression of iNOS in mesenteric vascular walls, whereas eNOS was unaffected. These findings, although extending to the mesenteric vascular district the concept that endotoxemia is associated with up-regulated iNOS expression (Hocherl et al, 2002), indicate that LPS-induced endothelial dysfunction is characterized by a significant reduction in stimulated NO availability. The different behavior of NOS isoforms in response to LPS (up-regulation of iNOS and unmodified eNOS expression), together with the reduced NO availability, is in line with a previous report on rabbit carotid arteries exposed to inflammatory cytokines (Kessler et al, 1997), showing that iNOS up-regulation was associated with an unmodified eNOS expression and an impaired endothelial function.…”
Section: Discussionmentioning
confidence: 78%
“…Concomitantly, we detected an enhanced expression of iNOS in mesenteric vascular walls, whereas eNOS was unaffected. These findings, although extending to the mesenteric vascular district the concept that endotoxemia is associated with up-regulated iNOS expression (Hocherl et al, 2002), indicate that LPS-induced endothelial dysfunction is characterized by a significant reduction in stimulated NO availability. The different behavior of NOS isoforms in response to LPS (up-regulation of iNOS and unmodified eNOS expression), together with the reduced NO availability, is in line with a previous report on rabbit carotid arteries exposed to inflammatory cytokines (Kessler et al, 1997), showing that iNOS up-regulation was associated with an unmodified eNOS expression and an impaired endothelial function.…”
Section: Discussionmentioning
confidence: 78%
“…This finding fits very well with the attenuation of LPS-induced hypotension by COX-2 inhibition. 12 In line with this, the positive effect of cPTIO on LPS-induced cardiovascular failure and mortality has been linked in part to an inhibition of PGI 2 synthesis via inactivation of PGIS. 32 Furthermore, it has been suggested that the induction of COX-2 in the heart is involved in myocardial dysfunction 33,34 and that increased PGI 2 synthesis via COX-2 could in part mediate LPS-induced cardiac failure.…”
Section: Discussionmentioning
confidence: 87%
“…12 Heart rate (HR), cardiac output (CO), systemic vascular resistance (SVR), and pressure were measured by a 2.0-Fr Millar tip catheter (Model SPR-838, Millar Instruments). A recovery period of 30 minutes was allowed to establish steady-state conditions.…”
Section: Measurement Of Hemodynamic Parametersmentioning
confidence: 99%
“…Because endotoxemia affects blood pressure (19,35), we first determined whether the blood pressures of wild-type and knockout mice were comparable before, during, and after hemorrhage/resuscitation. Before the imposition of hemorrhagic shock, the blood pressures of wild-type mice and knockout mice were nearly identical (Table 1).…”
Section: Resultsmentioning
confidence: 99%